2018
DOI: 10.1159/000494451
|View full text |Cite
|
Sign up to set email alerts
|

Distal Arthrogryposis with Impaired Proprioception and Touch: Description of an Early Phenotype in a Boy with Compound Heterozygosity of PIEZO2 Mutations and Review of the Literature

Abstract: The recessive PIEZO2-associated disease, distal arthrogryposis with impaired proprioception and touch (DAIPT), is characterized by hypotonia, perinatal respiratory distress, significantly delayed motor milestones, and progressive symptoms of distal arthrogryposis and scoliosis. Here, we describe the youngest patient with DAIPT to date, who, at the age of 3.5 years, did not show a single clinical sign of distal arthrogryposis or contractures, but had a history of bilateral clubfoot operations. On the contrary, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…Recently, a new family of nonselective cation channels in mammalian cells, known as "Piezo" (including Piezo1 and Piezo2), has been described in various mechanosensitive tissues and cells, including brain, heart, lung, liver, and kidney (3)(4)(5)(6). Although Piezo2 is a principal sensor for light touch and proprioception in mammals (7,8), Piezo1 is involved in the regulation of vascular development and blood pressure, lung growth, and injury (9)(10)(11)(12). Previous research showed that endothelial Piezo1 is required for the proper development of blood vessels (12)(13)(14)(15) by increasing phosphorylation of AKT or ERK and causing cell alignment through stretch-mediated Ca 2 þ influx and calpain activation or upregulation (10,(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a new family of nonselective cation channels in mammalian cells, known as "Piezo" (including Piezo1 and Piezo2), has been described in various mechanosensitive tissues and cells, including brain, heart, lung, liver, and kidney (3)(4)(5)(6). Although Piezo2 is a principal sensor for light touch and proprioception in mammals (7,8), Piezo1 is involved in the regulation of vascular development and blood pressure, lung growth, and injury (9)(10)(11)(12). Previous research showed that endothelial Piezo1 is required for the proper development of blood vessels (12)(13)(14)(15) by increasing phosphorylation of AKT or ERK and causing cell alignment through stretch-mediated Ca 2 þ influx and calpain activation or upregulation (10,(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Since proprioception is vital for motor and body control, patients with a loss of proprioception either due to an autoimmune disease [5] or due to a lossof-function mutation in a protein essential for proprioception [6] have prominent sensory and motor deficits, generally leading to ataxia and dysmetria. Patients with a congenital absence of proprioception show delayed development of head control and walking, an early impairment of fine motor skills, sensory ataxia with unsteady gait, increased stride-to-stride variability in force and step length, an inability to maintain balance with eyes closed (Romberg's sign), a severely reduced ability to identify the direction of joint movements, and an absence of tendon reflexes [6][7][8][9][10][11][12]. The motor problems are so severe that without the compensatory activity of other senses, including the vestibular and the visual systems, the patients are unable to maintain their posture, walk or perform coordinated voluntary movements.…”
mentioning
confidence: 99%
“…Biallelic loss-of-function pathogenic variants in PIEZO2 cause a specific DAIPT ( distal arthrogryposis with impaired proprioception and touch ) phenotype, including severe hypotonia with significant delay of motor milestones, transient respiratory distress and feeding problems in early infancy in addition to symptoms of severe progressive scoliosis and progressive contracture deformities of the hands and feet (Behunova et al, 2018 ). Congenital contractures of the feet are present in nearly all patients, whereas congenital contractures of the wrist or hands (including duck bill deformity) are present in most (Alper, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the same year Haliloglu et al described an 18-year-old boy. The heterozygous carriers (parents and siblings) were healthy (Behunova et al, 2018 ). In 2018, Behunova et al reported a three and a half year old boy, the youngest patient with DAIPT till that time.…”
mentioning
confidence: 99%